Integrated Transcriptome Analysis Reveals the Impact of Photodynamic Therapy on Cerebrovascular Endothelial Cells - He, Yanyan; Duan, Lin; Wu, Haigang; Chen, Song; Lu, Taoyuan; Li, Tianxiao; He, Yingkun (Frontiers in Oncology, 2021)
Blood vessels in brain tissue can form the compact vessel structure and play an essential role in maintaining the homeostasis of neurovascular system. Low dosage of photodynamic intervention significantly affected the expression of cellular biomarkers. To well understand the impact of photodynamic interventions on cerebrovascular endothelial cell, we performed the RNA sequencing and comet assay to evaluate the PDT of Porfimer sodium dependence on different dosage. By performing the functional analysis and protein-protein interaction, 15 hub genes are identified with the cellular mitosis process (CDK1, CDC20, MCM5, MCM7, MCM4, CCNA2, AURKB, KIF2C, ESPL1, BUB1B) and DNA replication (POLE2, PLOE, CDC45, CDC6). To performing the GSEA and leading-edge analysis, 8 up-regulated pathways and 45 down-regulated pathways have been identified. Activation of TNFα/NFκB and KRAS pathways indicated that photodynamic-induced activation of pathways may further affect the expression of transporter-related biomarkers. The identification of critical pathways and differentially expressed genes for PDT interventions suggests that low dosage of PDT intervention may be harmful for maintaining the homeostasis of BBB and inducing the inflammation response.